Implementation of CIPP Model in Social Studies Learning: A Literature Review - Affandri Jasrio; Ambiyar; Fahmi Rizal; Evida Safitri; Nofrion (Universitas Negeri Surabaya, 2026)
Comprehensive evaluation is crucial for enhancing the quality of social studies education. This literature review examines the implementation of the Context, Input, Process, and Product (CIPP) evaluation model in social studies learning contexts. The study employs a systematic literature review methodology, analyzing 45 peer-reviewed articles and scholarly works published between 2020 and 2025 from Scopus-indexed journals and reputable academic databases. The CIPP model, developed by Stufflebeam, provides a holistic framework for assessing educational programs across four dimensions: contextual relevance, resource adequacy, implementation effectiveness, and learning outcomes. Findings reveal that the CIPP model effectively identifies strengths and weaknesses in social studies curricula, enables data-driven decision-making, and facilitates continuous improvement in instructional practices. Context evaluation addresses alignment with educational policies and student needs; input evaluation assesses human resources, materials, and infrastructure; process evaluation monitors teaching-learning activities; and product evaluation measures achievement of learning objectives. The review identifies several implementation challenges, including limited evaluator expertise, insufficient stakeholder engagement, and resource constraints. Recommendations include developing comprehensive evaluation instruments, strengthening evaluator capacity through professional development, fostering collaborative evaluation cultures, and integrating technology-enhanced assessment tools. This study contributes to the theoretical understanding of evaluation frameworks in social studies education and provides practical guidance for educators and policymakers seeking to enhance program quality and student outcomes through systematic evaluation approaches.